MARKOVIAN MODELLING IN BUSINESS RISK ANALYSIS - Bosman, Stephan; Kruger, Paul S. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Risk analysis in a business context is largely intangible, allowing limited opportunity for the development of means by which the risk can be more securely assured, and in the long run, appropriately managed. This paper proposes that by means ofMarkovian analysis a basis can be established for the development of appropriate models. From the analysis , differential equations are established to solve into meaningful formulae for the system and solved via numerical methods . The use and development ofthis approach is' further illustrated by means of an example . AFRIKAANSE OPSOMMING: Risiko-analise, in die besigheidsomgewing, is 'n relatiefwasige vakgebied wat beperkte geleentheid bied vir die ontwikkeling van prosedures waarmee die risiko met groter sekerheid bepaal kan word en oor die langtermyn toepaslik bestuur kan word . In hierdie artikel word voorgestel dat Markovanal ise gebruik kan word om 'n basis te verskafvir die ontwikkeling van bruikbare modelle. Uitgaande van die analise kan differensiaalvergelykings opgestel word waarmee die gedrag van die stelsel beskryfkan word . Hierdie differensiaalvergelyking Ian met behulp van numeriese metodes opgelos word. Die gebruik en ontwikkeling van hierdie metodiek word geillustreer deur ' n voorbeeld.